Neurovascular and Immuno-Imaging: From Mechanisms to Therapies. Proceedings of the Inaugural Symposium - Akassoglou, Katerina; Agalliu, Dritan; Chang, Christopher J.; Davalos, Dimitrios; Grutzendler, Jaime; Hillman, Elizabeth M. C.; Khakh, Baljit S.; Kleinfeld, David; McGavern, Dorian B.; Nelson, Sarah J.; Zlokovic, Berislav V. (Frontiers in Neuroscience, 2016)
Breakthrough advances in intravital imaging have launched a new era for the study of dynamic interactions at the neurovascular interface in health and disease. The first Neurovascular and Immuno-Imaging Symposium was held at the Gladstone Institutes, University of California, San Francisco in March, 2015. This highly interactive symposium brought together a group of leading researchers who discussed how recent studies have unraveled fundamental biological mechanisms in diverse scientific fields such as neuroscience, immunology, and vascular biology, both under physiological and pathological conditions. These Proceedings highlight how advances in imaging technologies and their applications revolutionized our understanding of the communication between brain, immune, and vascular systems and identified novel targets for therapeutic intervention in neurological diseases.